When is research Artistic Research? - Correia, Jorge Salgado (2018)
Defining artistic research in a concise and unequivocal way seems to be as difficult as establishing boundaries and rules with which to frame it. Possibly because of this, some authors have been more interested in discussing when research can be considered artistic research than in proposing a clear-cut definition (Klein, 2017). In line with this point of view, this proposal represents an effort to launch the ground stones upon which an alternative path for Artistic Research may develop. Instead of an assertive, closed definition of Artistic Research, we are, in this first Cahier, launching the foundations on which to build, in the following Cahiers, a set of premises and principles - prolegomena - aimed at guiding the development of research projects. This alternative pathway will gradually progress along with (and because of) the growing set of research projects departing from these premises and principles. But first, we would like to highlight a number of introductory points, using examples, in the hope of further clarifying this matter.